2002
DOI: 10.1016/s0166-0934(01)00450-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of canine coronavirus antibodies by an enzyme-linked immunosorbent assay in dogs in the south of Italy

Abstract: An enzyme-linked immunosorbent assay (Elisa), using as antigen canine coronavirus-infected CrFK cell supernatant, was developed to detect antibodies against canine coronavirus (CCoV). Out of a total of 109 dog serum samples, 80 which were positive by routine virus neutralisation test were also Elisa positive. Seventeen samples which were negative by the virus neutralisation test, were positive by Elisa and by the confirmatory Western blotting test. The Elisa was substantially more sensitive than the virus neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 17 publications
4
50
0
Order By: Relevance
“…This could also explain the fact that there was no correlation between the seropositivity and factors such as sex and age of the animal. The frequency of antibodies against CCoV found in the wild canids of this study (38.5%) was in agreement with observed prevalence among the domestic canids (Pratelli et al, 2002;Caetano et al 2006;Dezengrini et al, 2007). The lower frequency of CCoV compared with CPV, was probably due to the biological characteristics of this virus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This could also explain the fact that there was no correlation between the seropositivity and factors such as sex and age of the animal. The frequency of antibodies against CCoV found in the wild canids of this study (38.5%) was in agreement with observed prevalence among the domestic canids (Pratelli et al, 2002;Caetano et al 2006;Dezengrini et al, 2007). The lower frequency of CCoV compared with CPV, was probably due to the biological characteristics of this virus.…”
Section: Discussionsupporting
confidence: 91%
“…The serum was inactivated at 56 °C for 30 minutes and then stored at -20 °C until further use. Antibodies to CDV and CCoV were determined by serum neutralization assays as described by Appel and Robson (1973) and Pratelli et al (2002). For CDV, serial two-fold serum dilutions starting from 1:10 were prepared in Eagle medium (MEM; Gibco BRL, UK), and incubated for one hour at 37°C with 100 TCID 50 of the Lederle strain of CDV.…”
Section: Methodsmentioning
confidence: 99%
“…Serological investigations carried out on a large number of dogs suggest that CCoV infection is widespread in pets and in kennel populations where seroprevalence may be particularly high (approximately 70-90%) [28,47]. In contrast, few data of gastroenteritis in dogs clearly attributable to CCoV have been reported 1 [1,19], and only a few strains have been adapted to grow in vitro.…”
Section: Canine Coronavirus Pathogenesismentioning
confidence: 99%
“…It has been shown that VN tests may fail to detect antibodies in some positive sera and thus provide misleading information on the epidemiology of the infection [28]. A recently developed ELISA was found to be more sensitive than the VN test, even though the antigen prepared from CCoV infected cells might yield variable results, depending on the method of antigen preparation [28]. Recently, it was demonstrated that antibodies against the M protein are detected consistently in seropositive dog sera after CCoV infection [7].…”
Section: Diagnostic Procedures and Vaccinationmentioning
confidence: 99%
“…The assessment of antibodies by the virus neutralization assay or by indirect enzyme-linked immunosorbent assay (ELISA) provides an indication of the protective immunity or, in unvaccinated animal, exposure to CCoV (MOCHIZUKI; SUGIURA; AKUZAWA, 1987;PRATELLI et al, 2002;PRATELLI et. al., 2003).…”
Section: Introductionmentioning
confidence: 99%